The Influence of Principal’s Leadership and the Role of School Committees on the Success of School-Based Management - Vermata, Triani Gusti; Lian, Bukman; Tobari, Tobari (Yayasan Sembilan Pemuda Indonesia, 2024)
A management style known as “school-based management” gives schools more autonomy and promotes direct participation from all students in decision-making processes. It is intended that through SBM, schools would be able to maximize their resources, minimize or perhaps completely eradicate their limits, and effectively address every challenge and threat that they confront on a local, national, and worldwide scale. Evaluation of student growth establishes whether the school meets or surpasses its quality criteria; the principal’s involvement is the decisive element in this regard. A school committee was established to use the resources already available to parents, the community, and the environment to support the direct and indirect implementation of education in schools. The purpose of this study is to ascertain how the leadership style of the principal and the function of the school committee affect the effectiveness of school-based management. In Sako District, Palembang, in a public elementary school, this study will be conducted. With a Fcount of 10.745 and a significance level of 0.000, correlational research using a sample of 76 teachers who were interviewed revealed that the school committee’s role and the principal’s leadership had a positive and significant impact on the success of school-based management. The leadership of the school principal and the function of the school committee account for 22.7% of the performance of school-based management, according to the results of the coefficient of determination test.